Bertud ng putik - Salvador, Augusto (Imus Production Inc., 2003)
The sin of the past is the tragedy of the present. The year is 1953 and Gabriel de Dios, a man who lives a simple and happy life with his family, possesses the good half of a powerful amulet. while Damian Buenavista, a black-hearted Scoundrel, who intends to rule the world owns the bad half. But Damian's plan to take control of the world will not be successful without the other half from Gabriel. Damian's plans, however, turn futile when Gabriel's bertud, as the amulet is called, saves Gabriel and brings him to the year 2003, Gabriel thinks he is already safe from the greedy Damian until he realizes the battle has just begun.